Patient-Centered Care in Mental Health: The Role of Psychiatrists, Nursing Technicians, and General Practitioners - Hossien Moteq Moshabab Alqahtani,; Yazeed Saleh Mohammed Alqahtani,; Ibrahim Ali Yahya Alasiri,; Mohammed Abdul Kareem Mohammed Alzemily,; Ali Hadi Mohammed Hadadi,; Ayed Mohamed Mohamed Alnaser,; Taghreed Mohamed Ali Alasiry,; Mohammed Amer Ali Al-Alamer,; Mohammed Abdullah Saeed Alrabie,; Sabah Abdullah Ahmed EyIlan, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The philosophy of patient-centered care involves providing health care that respects patients' needs, preferences, and feelings about their treatment at every stage of the care process. It advocates for a holistic model-that is, treatment considering a patient's emotional, social, and psychological needs in addition to, or even instead of, clinical symptoms-only for diagnostic purposes. Person-centered care fosters a collaborative and empathic atmosphere, giving patients the opportunity to become more active in their health. As a result, patients and health providers can develop more trustworthy therapy relationships. Psychiatrists, nursing technologists, and general practitioners will contribute to such a seamless multidisciplinary framework, since each individual brings forth different knowledge and opinions that complement one another. Psychiatrists diagnose and measure the treatment; they also tailor treatment programs while encouraging open communication with the patients and their relatives. Nursing technicians monitor daily activities and offer emotional support that helps bridge communications between the patients and other members of their healthcare team. General practitioners bring in their wide view on physical health by managing co-occurring conditions and encouraging a holistic approach toward recovery. It discusses in detail the specific roles of providers at Abha Eradah and Mental Health Hospital, integrated efforts in coordinating care in a patient-centered care framework to increase quality and effectiveness in the delivery of mental health services. By being in tune with each patient's needs and encouraging active involvement in the team at Abha Eradah, this emphasizes the power of a patient-centered approach to care as it shapes mental health settings toward greater patient satisfaction and better overall long-term health outcomes. Accordingly, this way the mental health team will be better placed to address intractable health problems, changing patients' needs, and therefore contribute to sustainable recoveries and quality lives.